Achieving Both Creativity and Rationale: Reuse in Design with Images and Claims - McCrickard, Scott; Wahid, Shahtab; Branham, Stacy; Harrison, Steve (Human Technology, 2011)
Although designers often try to create novel designs, many designs are based on previous work. In this paper we argue for the reuse of rationale, in the form of claims, as a central activity in design, and explore how this can be used to inspire creativity. We present a design activity in which images and claims are reused to create a storyboard and illustrate how creativity and rationale complement each other. Our work serves to demonstrate that an appropriate design activity can be used to leverage creativity with the use of rationale.